Individual and Neighborhood Characteristics of Walking Activity in People Living With Dementia: A Proof of Concept for Quantitative Spatial Analysis. - Nouri, Mohammadjavad; Chaudhury, Habib (Journal of Aging & Physical Activity, 2025)
Background/Objectives: Creating dementia-friendly neighborhoods is crucial for enhancing outdoor walking activity and maintaining social participation among people living with dementia (PLWD). This study utilizes GPS and geographic information system technologies to conduct a quantitative spatial analysis, revealing how individual and neighborhood characteristics are associated with PLWD's walking activity characteristics. Methods: Twenty-five participants from Metro Vancouver had their regular walking routes (RWR) from home to neighborhood destinations recorded using GPS technology. Spatial analysis tools and existing survey data were utilized to construct the research geodatabase. Nonparametric tests (Spearman's rank correlation, Kendall's tau, and Mann–Whitney) and parametric tests (Pearson correlation and point biserial) assessed associations between independent variables, including sociodemographic characteristics of participants (e.g., age and health) and their neighborhoods (e.g., age structure and language barriers), and built environment features (e.g., land use diversity), with two dependent variables: length of RWR and walking time to regular destination within the 20-min walkshed. Results: Longer RWR and increased walking time to regular destination within the 20-min walkshed are associated with fewer physical health limitations, gentler terrain, proximity to green spaces, and bus stops. In addition, higher land use diversity, proximity to secondary streets, integrated sidewalks, higher number of benches and intersections, and a slight street network curvature showed positive associations with RWR length and walking time to regular destination within the 20-min walkshed. Conclusion: GPS and geographic information system technologies provide a unique quantitative method for understanding mobility patterns among PLWD. While limited by participant numbers, this exploratory study provides directions for future investigations. Significance/Implications: This study offers insights into designing dementia-friendly neighborhoods that support social engagement and physical activity among PLWD.